Development of Learning Tools Model (CIRC) With Portfolio Assessment to Improve Indonesian Writing Skills in Grade V Elementary School - Rinjani, Pelangi Bening; Wulandari, Murfiah Dewi (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2024)
Since elementary school, students have been taught six basic literacies. Literacy skills are fundamental skills that need to be owned and mastered by every indi-vidual. One of the components that determine the success rate of language learn-ing is the ability to write, read and count, which are basic literacy skills. The pur-pose of this development research is to, 1) identify factors that cause elementary school students to have low writing skills, 2) develop learning tools based on the CIRC model with portfolio assessment that are valid, practical, and effective as an effort to improve the writing skills of grade V elementary school students. This research is a Research and Development (R&D) development research that adopts the ADDIE model with Analysis, Design, Development, Implementation, and Evaluation processes. This study used observation, interviews, question-naires, writing skills tests, and pre-test post-test questions to collect data. Mean-while, validity, practicality, and normalized gain (N- gain) tests were used to ana-lyze the data. Based on the validity test of material experts and media experts conducted by the two validators, the average scores were 87% (valid) and 85% (valid), respectively. Then, from filling out the practicality questionnaire by the teacher, an average score of 88.6% (very practical) was obtained. Finally, the re-sults of filling out the pre-test and post-test questions by students obtained an N-gain result of 0.57 (medium). Thus, the teaching module based on the CIRC model with portfolio assessment can be declared valid, practical, and effective for improving the writing skills of grade V elementary school students.